2018
DOI: 10.1007/s11858-018-0974-9
|View full text |Cite
|
Sign up to set email alerts
|

Middle school students’ reasoning about data and context through storytelling with repurposed local data

Abstract: Publicly-available datasets, though useful for education, are often constructed for purposes that are quite different from students' own. To investigate and model phenomena, then, students must learn how to repurpose the data. This paper reports on an emerging line of research that builds on work in data modeling, exploratory data analysis, and storytelling to examine and support students' data repurposing. We ask: What opportunities emerge for students to reason about the relationship between data, context, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Thus the author suggested that "both data-context and learning-experience-contexts may need to be taken into account when developing learners' reasoning from data" (Pfannkuch, 2011, p. 43). Similar observations are reported in the literature on the relationships between data and context (e.g., Ben-Zvi & Aridor-Berger, 2016;Wilkerson & Laina, 2018).…”
Section: Contextsupporting
confidence: 88%
“…Thus the author suggested that "both data-context and learning-experience-contexts may need to be taken into account when developing learners' reasoning from data" (Pfannkuch, 2011, p. 43). Similar observations are reported in the literature on the relationships between data and context (e.g., Ben-Zvi & Aridor-Berger, 2016;Wilkerson & Laina, 2018).…”
Section: Contextsupporting
confidence: 88%
“…What types of instruction and supports enable students to gain confidence in manipulating data? Some studies (e.g., Wilkerson & Laina, 2018) are emerging, but we need more. To save the reader from even more exposition-for the time being-we will simply present a slew of potential questions that could be explored:…”
Section: What Else Should We Think About and Do?mentioning
confidence: 99%
“…In doing so, our project recognizes that a great deal of conceptual and personal work goes into students' initial preparation and exploration of data. For example, students may seek a grounding in the data by filtering and searching a dataset to find specific records that represent themselves or other familiar information [18,21]. Or, they might want to reduce the complexity of their initial investigation by focusing on only a few key attributes of a large dataset, expanding their investigation later [7].…”
Section: Introductionmentioning
confidence: 99%